Quintuplets of orthoprojectors associated by a linear relation - Yusenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider the equation α_1 P_1 + α_2 P_2 + … α_n P_n = I over orthoprojectors P_1, … ,P_n in a Hilbert space. We show that the set of real parameters (α_1, … α_n) for which there exists a solution of this equation in orthoprojectors contains an open set from ℝ^5.